Inequality, income and poverty: Comparative global evidence - Augustin Kwasi Fosu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Analysing a large sample of 1980 - 2004 unbalanced panel data, the current study presents comparative global evidence on the role of (income) inequality in poverty reduction. The evidence involves both an indirect channel via the tendency of high inequality to decrease the rate at which income is transformed to poverty reduction and the tendency of rising inequality to increase poverty. Based on the basic needs approach, an analysis-of-covariance model is estimated, with the headcount measure of poverty as the dependent variable and the Gini coefficient and PPP-adjusted mean income as explanatory variables. The study finds that the responsiveness of poverty to income growth is a decreasing function of inequality and that the income elasticity of poverty is actually smaller than the inequality elasticity. Thus, income distribution can play a more important role than might be traditionally acknowledged. Found also is a large variation across regions (and countries) in the poverty effects of inequality.
Keywords: D31; I32; O49; 330; inequality; income; poverty; comparative global evidence; Soziale Ungleichheit; Einkommensverteilung; Armutspolitik; Welt